MOTHER’S FIRST EXPERIENCE IN ASSISTING CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKEMIA WHO IS UNDERGOING CHEMOTHERAPY - Dwi Novrianda; Fini Alfi Anita (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Acute Limfoblastic Leukemia (ALL) is a malignant disease which mostly found in children. The main treatment of ALL is chemotherapy for a long time, so it affects their mother life as the primary caretaker. This research aimed to explore, understand, and give the meaning of mother’s fi rst experience in assisting children with ALL that was undergoing chemotherapy: the induction phase. Method. This research was a qualitative research by using phenomenological. Six participants were taken by using purposive sampling that participated in interview. In-depthinterviews and fi eld note were used to collect data. The result of the interview was transcribed verbatimly and analyzed by Collaizi method. Results. There was six main themes that found in this research including:1) undergoing emotional response, 2) undergoing physical impaired, 3) seeking information, 4) undergoing a spiritual experience, 5) undergoingan economic burden, and 6) the importance of support. Discussion. It suggests that nurses provided nursing care to mother that assisting the children in chemotherapy at the fi rst time like giving intervention concerned emotional problem, physical, and spiritual. It also gives earlier information for mother about chemotherapy.Keywords: mother’s fi rst experiences, chemotherapy, induction phase, acute lymphoblastic leukemia’s children